Mood and Personality Characteristics are Associated with Metamemory Knowledge Accuracy in a Community-Based Cohort of Older Adults. (5th February 2018) - Colvin, Leigh E.; Malgaroli, Matteo; Chapman, Silvia; MacKay-Brandt, Anna; Cosentino, Stephanie
Abstract: Objectives: Emerging work reveals the neuroanatomic changes that compromise metacognition; however, little is known about the impact of premorbid factors. Research suggests that psychological variables influence the perception of cognition, but whether they influence the accuracy of those perceptions (i.e., metacognition) has not been directly examined.Participants and Methods: Using Latent Class Analysis (LCA), we tested for discrete personality (NEOFFI) and mood (STAI, BDI-II, and GDS) classes among a community-based cohort of 151 older adults, enrolled in the NKI-Rockland study. Metamemory was calculated by comparing subjective memory ratings (modified Cognitive Failures Questionnaire) to objective memory (Rey Auditory Verbal Learning Test) to determine the degree to which individuals were overconfident, underconfident, or accurate in their self-assessment. A generalized linear model was used to examine whether metamemory differed across the emergent classes. A one sample t test was used to determine whether the metamemory scores of the emergent classes were statistically significantly different from zero, that is, over or under confident.Results: Two discrete classes emerged in the LCA: Class 1 was characterized predominantly by high extraversion and conscientiousness and low neuroticism and anxiety; Class 2 was characterized predominantly by low extraversion and conscientiousness and high neuroticism and anxiety. Metamemory differed significantly as a function of Class Membership ( F (4, 151)=5.42; p <.001), with Class 1 demonstrating accurate metamemory (M=0.21; SD =1.31) and Class 2 demonstrating under-confidence (M=−0.59; SD =1.39) in their memory.Conclusions: The significant association between psychological factors and metamemory knowledge accuracy suggests that such characteristics may be important to consider in the conceptualization, assessment, and treatment of metacognitive disturbances. ( JINS, 2018, 24, 498–510)